2019
DOI: 10.1108/bij-04-2018-0086
|View full text |Cite
|
Sign up to set email alerts
|

Using integrated weighted IRP-Fuzzy TISM approach towards evaluation of initiatives to harmonise Halal standards

Abstract: Purpose Multiplicity and conflicting Halal standards involve unnecessary repetition of testing for demonstrating the Halal integrity of the process and the product, thus making it difficult for the Halal commodities to get traction in international markets. The purpose of this paper is to suggest initiatives to facilitate harmonisation of Halal standards as to eliminate trade barrier of Halal and to assure the availability of Halal consumables to larger masses. Design/methodology/approach Ranking of the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 70 publications
0
24
0
2
Order By: Relevance
“…It suggests that firms are striving for Halal food safety certification in response to the growing demand for Halal food products and rising concern among the consumers over the series of foodborne illnesses. Khan et al (2019a) using integrated interpretive modelling evaluated initiatives which facilitate the harmonisation of Halal standards by considering the cost of accomplishment and associated benefits. Haleem et al (2019) have identified and analysed the barriers towards the adoption of Halal certification assessment and accreditation using interpretive structural modelling.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It suggests that firms are striving for Halal food safety certification in response to the growing demand for Halal food products and rising concern among the consumers over the series of foodborne illnesses. Khan et al (2019a) using integrated interpretive modelling evaluated initiatives which facilitate the harmonisation of Halal standards by considering the cost of accomplishment and associated benefits. Haleem et al (2019) have identified and analysed the barriers towards the adoption of Halal certification assessment and accreditation using interpretive structural modelling.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considering the extra cost of halal-certified products and consumers' price concerns, Zailani et al (2017) suggested, from a business point of view, that JAKIM, HDC and halal companies should collaborate with each other to set standards that secure the halal integrity of their products throughout the whole supply chain while maintaining cost effectiveness. Khan et al (2019b) emphasized the importance of harmonizing globally agreed halal standards for halal practices to influence the international trade of halal commodities. Although collaboration of halal companies may reduce the cost of halal certification, it is time-consuming, and with respect to this concern, it is, therefore, crucial for halal companies to understand the factors that motivate Muslim consumers to pay extra for halal-certified products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, this will also contribute positively to social tolerance. Khan et al, (2019) has researched how harmonization of halal can be done, in his research entitled Using integrated weighted IRP-Fuzzy TISM approach towards evaluation of initiatives to harmonise Halal standards has an objectivesuggest initiatives to facilitate harmonisation of Halal standards as to eliminate trade barrier of Halal and to assure the availability of Halal consumables to larger masses. With Ranking of the initiatives for the harmonisation of Halal standards taking in consideration the costs of accomplishment and associated benefits obtained has been done through the application of integrated Interpretive Ranking Process (IRP) and Fuzzy Total Interpretive Structural Modelling (Fuzzy TISM).…”
Section: Resultsmentioning
confidence: 99%